Interpersonal Closeness Correlates With Social Influence on Color Perception Task Using Human and Artificial Agents - Tatsukawa, Kyohei; Takahashi, Hideyuki; Yoshikawa, Yuichiro; Ishiguro, Hiroshi (Frontiers in ICT, 2018)
It is well known that artificial agents, such as robots, can potentially exert social influence and alter human behavior in certain situations. However, it is still unclear what specific psychological factors enhance the social influence of artificial agents on human decision-making. In this study, we performed an experiment to investigate what psychological factors predict the degree to which human partners versus artificial agents exert social influence on human beings. Participants were instructed to make a decision after a partner agent (human, computer, or android robot) answered the same question in a color perception task. Results indicated that the degree to which participants conformed to the partner agent positively correlated with their perceived interpersonal closeness toward the partner agent. Moreover, participants’ responses and accompanying error rates did not differ as a function of agent type. The current findings contribute to the design of artificial agents with high social influence.